Fashion branding unraveled - Hameide, Kaled K. (Fairchild Books, 2011)
"This book presents a complete view of fashion branding, from the concept of branding to the dynamics of the branding process. It explores the application of concepts to the different categories of the fashion brand, such as luxury brands and private labels, and discusses specific branding strategies related to the fashion industry as practiced today."--Publisher's description.